An Abundance of Selves: Young Adults' Narrative Identities While Living With Cancer. Issue 1 (January 2017) - Hammond, Chad; Teucher, Ulrich
Abstract : Background: Identity negotiations of people living with cancer have been shown to be significant psychosocial challenges throughout cancer trajectories but have not been adequately explored among young adults with cancer. Narrative approaches might help to reveal moments of (dis)empowerment that affect their identity negotiations. Objective: The aim of this study is to explore how young adults speak to their identities in relation to their narratives of having cancer and receiving care. Methods: A total of 21 young adults (18–45 years old) provided cancer narratives through semistructured life history interviews. Thematic narrative analysis was used to determine how participants represented themselves in their stories. Results: Participants used a wide diversity of identities well beyond those most familiar in dominant discourses (eg, patients, survivors, and fighters), and their identities frequently changed at significant "turning points" in their narratives, especially in relation to good and bad experiences of care. Conclusions: Cancer-related identities often undergo personal and social negotiation over time, and not just among young adults still feeling the effects of treatment. Psychosocial oncology could take further steps toward incorporating this fluidity and multiplicity within the discipline's discourses of identity. Implications for Practice: The identities gathered here may contribute to a more comprehensive toolkit of narrative resources for empowering young adults (and others) with cancer, serving as a starting point for negotiating identities with their care providers. Our findings raise questions about which identities should be fostered and how healthcare professionals might be (unknowingly) involved in patients' identity negotiations.